2010
DOI: 10.1542/peds.2010-1839
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events From Cough and Cold Medications After a Market Withdrawal of Products Labeled for Infants

Abstract: WHAT'S KNOWN ON THIS SUBJECT:A voluntary market withdrawal of orally administered, over-the-counter cough and cold medications (CCMs) labeled for infants was announced in October 2007 because of concerns regarding limited evidence of efficacy and potential harmful effects of these products among young children. WHAT THIS STUDY ADDS:This study assessed changes in CCMrelated harm, as measured with national estimates of emergency department visits for CCM-related adverse events, among children after announcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
0
27
0
5
Order By: Relevance
“…We assessed ED visits involving children 2 to 11 years old before and after October 1, 2008, because previous studies found that the 2007 withdrawal of infant products had not significantly affected CCM ADEs among children $2 years old. 1,10 Each NEISS-CADES case is assigned a sample weight based on the inverse probability of selection. The sample weights are modified for nonresponse rate and poststratified to adjust for the number of annual hospital ED visits.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed ED visits involving children 2 to 11 years old before and after October 1, 2008, because previous studies found that the 2007 withdrawal of infant products had not significantly affected CCM ADEs among children $2 years old. 1,10 Each NEISS-CADES case is assigned a sample weight based on the inverse probability of selection. The sample weights are modified for nonresponse rate and poststratified to adjust for the number of annual hospital ED visits.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Studies had not demonstrated CCMs to be more effective than placebo in young children but had linked CCMs to significant numbers of emergency department (ED) visits and, in rare cases, infant deaths. [5][6][7][8] The Food and Drug Administration (FDA) formally supported this withdrawal in January 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Setelah rekomendasi (2007) tersebut, kunjungan pasien ke unit gawat darurat akibat efek merugikan berkurang menjadi setengahnya. 1,3,4 Beberapa perusahaan juga telah mengikuti rekomendasi tersebut dengan mengubah label produknya untuk tidak digunakan pada anak usia dibawah 4 tahun. Sedangkan American Academy of Pediatrics (AAP) merekomendasikan untuk tidak menggunakan obat batuk pilek yang dijual bebas pada anak usia di bawah 6 tahun.…”
Section: Hasilunclassified
“…[11] Another medicine Clonidine suspension is mostly prescribed to children and the overdose of Clonidine in children has resulted in major clinical circumstances and lead to deaths. [12,13] According to FDA (Food and Drug Administration) calibration for measuring devices should be within value of ±5% which is assigned for Measuring Devices, Packaging, Medication Safety Containers. [14] …”
Section: Introductionmentioning
confidence: 99%